Acute effects of three warm-up protocols on drop jump biomechanics in elite Taekwondo athletes: An IMU-based analysis - Somayeh Taghidoust Chahardeh; Seyyed Hossein Hosseini; Ali Shamsi Majelan (PLoS ONE, 2026)
This randomized, parallel-group pre–post study examined the acute effects of three warm-up modalities on stretch–shortening cycle (SSC) biomechanics in elite female Taekwondo athletes. Thirty-six participants were randomly assigned to dynamic stretching, foam rolling, or resistance-band (TheraBand) protocols following a standardized submaximal treadmill warm-up. Three-dimensional kinetic and temporal variables were collected during drop jump tasks before and after each intervention using inertial measurement units.Between-group post-intervention differences were analyzed using analysis of covariance (ANCOVA) or rank-based Quade’s ANCOVA, controlling for baseline disparities. Within-group changes were assessed using paired parametric or non-parametric tests as appropriate. Effect sizes (η²) are reported alongside p-values to indicate the magnitude of observed effects.Significant group effects were observed for concentric phase duration (η² = 0.177), peak concentric force (η² = 0.186), and mean concentric power (η² = 0.211). Post-hoc analyses revealed that dynamic stretching enhanced concentric force and power, while foam rolling primarily altered temporal characteristics of force development. TheraBand preserved performance close to baseline. In contrast, gross performance outcomes such as jump height, flight time, and contact time showed trivial effect sizes (η² ≤ 0.104) and no significant between-group differences. These findings indicate that warm-up modalities selectively modulate force- and power-related components of SSC function rather than uniformly enhancing overall jump performance. By ‘selective modulation,’ we mean that different warm-up protocols influence distinct components of stretch-shortening cycle function rather than producing a generalized enhancement. Specifically, dynamic stretching primarily improved concentric force and power output; foam rolling altered temporal characteristics (e.g., concentric duration and time to peak power) without increasing peak force; and TheraBand preserved baseline performance across most variables. This selective response indicates that warm-up modality should be matched to the specific neuromuscular demand of the subsequent task. Post-hoc comparisons clarify which groups differ, highlighting the practical utility of dynamic stretching for enhancing propulsive-phase mechanics in elite athletes.